2018
DOI: 10.4171/jems/850
|View full text |Cite
|
Sign up to set email alerts
|

All couplings localization for quasiperiodic operators with monotone potentials

Abstract: We establish Anderson localization for quasiperiodic operator families of the formfor all λ > 0 and all Diophantine α, provided that v is a 1-periodic function satisfying a Lipschitz monotonicity condition on [0, 1). The localization is uniform on any energy interval on which Lyapunov exponent is bounded from below. 1 1 We employ the word non-perturbative in the widely used by now sense of "obtained as a corollary of positive Lyapunov exponents without further largeness/smallness assumptions" [9,28].2 Maryland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…They showed that the Lyapunov exponent is smooth or even analytic, respectively. Besides, for a 1-periodic function satisfying a Lipschitz monotonicity condition, Jitomirskaya and Kachkovskiy [25] showed that the Lyapunov exponent is almost Lipschitz continuous.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the Lyapunov exponent is smooth or even analytic, respectively. Besides, for a 1-periodic function satisfying a Lipschitz monotonicity condition, Jitomirskaya and Kachkovskiy [25] showed that the Lyapunov exponent is almost Lipschitz continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Another immediate corollary can be obtained for a class of discontinuous f monotone on the period as considered in [15]. Then, Anderson localization is established in [15] for Diophantine ω, while continuity (and positivity for large λ) of the Lyapunov exponent is established for all ω. Theorem 1.7 immediately implies in this case vanishing of β − for λ as above and all θ and all ω.…”
Section: Corollary 113mentioning
confidence: 93%
“…The latter is a general result that is of independent interest and of the type that has been crucial in various proofs of localization/regularity in many recent articles. Our extension has already been used in [15] for their spectral localization theorem and in [21] for their dimensional analysis of Sturmian potentials.…”
Section: Corollary 113mentioning
confidence: 99%
See 1 more Smart Citation
“…A natural generation of the potential x mod 1 is the so called Lipschitz monotone potential, which was introduced recently by [JK19]. In [JK19], the authors proved all couplings localization for the 1D Schrödinger operator with a Lipschitz monotone potential. • By δ ij we denote the Kronecker delta.…”
Section: Pöschel (Seementioning
confidence: 99%